2009
DOI: 10.1002/elan.200804538
|View full text |Cite
|
Sign up to set email alerts
|

Metal On‐Line Voltammetric Analyzer for On‐Site Monitoring of Iron Speciation in Acid Mine Drainage Waters: Development and Characterization

Abstract: The development of a simple, low cost, portable metal on-line voltammetric analyzer (MOVA) for the iron analysis, as well as other species, in mining effluents is presented. It consists of a voltammetric cell based on an impinging jet flow configuration, a fluidic system controlled by gravity and electronics. Laboratory tests were performed to optimize the system as well as the analytical conditions for Fe speciation measurements. MOVA was then tested in the laboratory, in samples of both mining effluents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…1ii) at intermediate potentials. First, we note that the effect of dissolved oxygen in voltammetric studies of Fe has been studied, 22 but in our experiments we have purged the solutions with nitrogen and therefore these peaks are not related to oxygen reduction. In the concentration range 1-10 mM, the formation of significant quantities of dinuclear and multinuclear Fe species is known and is responsible for the reddish colour of aqueous Fe(III).…”
Section: Speciation Of Fe(iii) and Fe(ii)-voltammetric Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1ii) at intermediate potentials. First, we note that the effect of dissolved oxygen in voltammetric studies of Fe has been studied, 22 but in our experiments we have purged the solutions with nitrogen and therefore these peaks are not related to oxygen reduction. In the concentration range 1-10 mM, the formation of significant quantities of dinuclear and multinuclear Fe species is known and is responsible for the reddish colour of aqueous Fe(III).…”
Section: Speciation Of Fe(iii) and Fe(ii)-voltammetric Studiesmentioning
confidence: 99%
“…18 Some voltammetric studies of dissolved iron relevant to acid minewater disharge have been reported, however their focus has mainly been on electrochemical remediation, 19 fundamental studies of bacterial iron respiration related to mine-water remediation, 20,21 or the development of portable equipment. 22 In this report, we show how voltammetric techniques can be employed to measure, not only total iron ([Fe] total ), but also dissolved ([Fe] aq ) and solid-phase iron ([Fe] sol ). We further show that voltammetric techniques are sensitive to aspects of iron speciation in mine-water, including the presence of hydrolysed versus unhydrolysed Fe ([Fe] hyd , [Fe] unh ), and that they can be used to monitor the ratio of Fe(II) and Fe(III) redox states.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of a suitable working electrode is the crucial part of a successful voltammetric measurement. For the determination of Fe(III), various working electrodes including mercury film [12], mercury drop electrode [16][17][18], glassy carbon [13,19], gold [20], Bi film and Bi nanosheet [21,22], and bismuth bulk annular electrodes [23] have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of automated electroanalytical device was reported by Hezard et al for Fe(III) and Fe(II) quantification in acid mining drainage water (Hezard et al, 2009 ). In this particular case, the redox species were concentrated enough to allow direct determination using an unmodified Pt electrode.…”
Section: Introductionmentioning
confidence: 99%